ANALISIS KEUNGGULAN BERSAING BERKELANJUTAN METRASAT DALAM INDUSTRI VSAT DI INDONESIA - , Socfin Butar Butar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
VSAT is a communication based on satellite. In Indonesia, VSAT business is still profitable and has a huge revenue. With that huge revenue, the competition becomes increase among each satellite providers in Indonesia. Now, MetraSat which one of satellite provider also in Indonesia is on the highest rating in VSAT market share. This is because of the impact of internal and external factors on MetraSat itself. Beside that, aggresive posisiton and the quality of human resources also have impact in increasing the performance of MetraSat. In order to compete with other competitor, MetraSat must have competition advantages better than others such as affordable price, flexibility of bandwith, quality and network safety, better technology server especially service level agreeement that reached highest point at 99%. By those all competitive advantages, hopefully MetraSat becomes more bigger and still do exist in comptetiton of VSAT industry.